Deleterious Rare Mutations of GLI1 Dysregulate Sonic Hedgehog Signaling in Human Congenital Heart Disease - Peng, Rui; Li, Binbin; Chen, Shuxia; Shi, Zhiwen; Yu, Liwei; Gao, Yunqian; Yang, Xueyan; Lu, Lei; Wang, Hongyan (Frontiers in Cardiovascular Medicine, 2022)
The Glioma-associated oncogene (Gli) family members of zinc finger DNA-binding proteins are core effectors of Sonic hedgehog (SHH) signaling pathway. Studies in model organisms have identified that the Gli genes play critical roles during organ development, including the heart, brain, kidneys, etc. Deleterious mutations in GLI genes have previously been revealed in several human developmental disorders, but few in congenital heart disease (CHD). In this study, the mutations in GLI1-3 genes were captured by next generation sequencing in human cohorts composed of 412 individuals with CHD and 213 ethnically matched normal controls. A total of 20 patient-specific nonsynonymous rare mutations in coding regions of human GLI1-3 genes were identified. Functional analyses showed that GLI1 c.820G> T (p.G274C) is a gain-of-function mutation, while GLI1 c.878G>A (p.R293H) and c.1442T>A (p.L481X) are loss-of-function mutations. Our findings suggested that deleterious rare mutations in GLI1 gene broke the balance of the SHH signaling pathway regulation and may constitute a great contribution to human CHD, which shed new light on understanding genetic mechanism of embryo cardiogenesis regulated by SHH signaling.